Toxicity of Tetradium ruticarpum: Subacute Toxicity Assessment and Metabolomic Identification of Relevant Biomarkers - Shan, Qiyuan; Tian, Gang; Han, Xin; Hui, Hui; Yamamoto, Mai; Hao, Min; Wang, Jingwei; Wang, Kuilong; Sang, Xianan; Qin, Luping; Chen, Guanqun; Cao, Gang (Frontiers in Pharmacology, 2022)
Tetradium ruticarpum (TR) is widely used in Asia to treat gastrointestinal disorders and pain. Stir-frying with licorice aqueous extract is a traditional processing procedure of TR formed in a long-term practice and performed before clinical application, and believed to reduce TR’s toxicity. However, its toxicity and possible toxicity attenuation approach are yet to be well investigated. Subacute toxicity and metabolomics studies were conducted to help understand the toxicity of TR. The subacute toxicity assessment indicated that 3 folds of the recommended therapeutic dose of TR did not show obvious subacute toxicity in rats. Although extremely high dose (i.e. 60 folds of recommended dose) may cause toxicity in rats, it reversed to normal after 2 weeks of recovery. Hepatocellular injury was the major toxic phenotype of TR-induced liver damage, indicating as AST and liver index increasing, with histopathologic findings as local hepatocyte necrosis, focal inflammatory cell infiltration, slightly bile duct hyperplasia, and partial hepatocyte vacuolation. Moreover, we evaluated the impact of processing in toxicity. TR processed with licorice could effectively reduce drug-induced toxicity, which is a valuable step in TR pretreatment before clinical application. Metabolomics profiling revealed that primary bile acid biosynthesis, steroid biosynthesis, and arachidonic acid metabolism were mainly involved in profiling the toxicity metabolic regulatory network; the processing procedure could back-regulated these three pathways, may be in an AHR dependent manner, to alleviate the metabolic perturbations induced by TR. 7α-hydroxycholesterol, calcitriol, and taurocholic acid were screened and validated as the toxic biomarkers of TR for potential clinical translation. Overall, the extensive subacute toxicity evaluation and metabolomic analysis would not only expand knowledge of the toxicity mechanisms of TR, but also provide scientific insight of traditional processing theory, and support clinical rational use of TR.